Awareness of meaning and quest for meaning: The mechanisms between future orientation and prosociality among youth during pandemic - Lui, Wai-Kin; Chan, Chi-Keung; Ng, Kai-Hang; Chui, Chi-Fai Raymond; Siu, Nicolson Yat-Fan; Yung, Chui-Shan; Lau, Ka-Wing (Frontiers in Psychology, 2022)
Introduction The positive relationship between future orientation and prosocial tendency has been consistently reported. However, the possible mechanism has not been examined yet. Previous research revealed the positive relationship between future orientation and meaning in life, as well as between meaning in life and prosocial tendency. Hence, it is hypothesized that the two components of meaning in life (presence of meaning and search for meaning) possibly mediate the relationship between future orientation and prosocial tendency. Methods During the first half of 2020, 430 Hong Kong youths aged 15–35 (male: 30.5%; female: 69.5%) were recruited to participate an online cross-sectional survey. The survey included three scales: (1) The Scale for Measuring Adult’s Prosocialness, (2) Consideration of Future Consequence Scale, and (3) Meaning in Life Questionnaire. Results The key findings showed that: (1) females had higher level of prosocial tendency than males, and (2) significant partial mediating effects of both presence of meaning and search for meaning on the relationship between future orientation and prosocial tendency. Nevertheless, the multi-group mediation model did not show significant gender difference. Discussion These findings implied that future-oriented and meaning-focused interventions could possibly enhance youth’s sense of meaning in everyday life and foster their meaning searching tendency, which further strengthen the positive effect of their future orientation on prosocial tendency, even during life adversities.